Design thinking in medical ethics education. Issue 4 (13th February 2020) - Marcus, David; Simone, Amanda; Block, Lauren
Abstract : Background: Design thinking (DT) is a tool for generating and exploring ideas from multiple stakeholders. We used DT principles to introduce students to the ethical implications of organ transplantation. Students applied DT principles to propose solutions to maximise social justice in liver transplant allocation. Methods: A 150 min interactive workshop was integrated into the longitudinal ethics curriculum. Following a group didactic on challenges of organ donation in the USA supplemented by patient stories, teams of students considered alternative solutions to optimise fairness of organ distribution and ethical implications of changing the current model. Facilitators led students through DT steps of empathy, defining the team's point of view, ideating on potential solutions, prototyping a specific idea and testing the idea through oral presentation, with questions and answers by peers and faculty. The curriculum was evaluated with presurveys and postsurveys including quantitative and open-ended items. Results: 100 first year medical students participated. Before the session, 75.3% of students had no practical experience with DT. Following participation, students reported an increased understanding of the current liver transplant allocation system (p<0.01) and an increased appreciation of shortcomings of the current organ allocation system (p<0.01). After the session, 73.8% of students felt that DT could be used to approach complex health system problems. Discussion: Students participating in a DT workshop displayed improved knowledge and attitudes toward organ transplantation and DT. In this pilot study, DT showed promise as a student-led approach emphasising collaboration and creativity in ethics curricula in medical education.